Visual Evoked Potentials in Neuromyelitis Optica Spectrum Disorders. (20th December 2021) - Hernandez Fustes, Otto Jesus; Kay, Cláudia S K; Lorenzoni, Paulo José; Ducci, Renata D-P; Werneck, Lineu C; Scola, Rosana Herminia
Background: Neuromyelitis optica spectrum disorders (NMOSDs) are rare antibody-mediated disorders of the central nervous system, with a predilection for the spinal cord and optic nerves. The clinical utility of evoked potential recordings (EPs) has already been established for multiple sclerosis, in particular, that of the abnormal visual evoked potentials (VEP), a key criterion in the McDonald diagnostic criteria for MS. However, there have been few reports on EPs in patients with NMOSD. AIM: The aim of our study was to assess the possible involvement of the optical pathway through VEP responses in patients with NMOSD. Methods: VEPs were prospectively performed in 13 patients with NMOSD. All the patients were recruited from the outpatient clinic of a demyelinating diseases center. The recording was done as recommended by the International Federation of Clinical Neurophysiology. Results: We evaluated the eyes of 12 women with a mean age of 42 years and of one man who was 25 years old. In 6 of the examined eye samples, a response was not obtained, while in the remaining 20 eye samples, we found a significant increase in P100 latency without amplitude change. Conclusion: VEPs showed a significant increase in P100 latency. VEP assessment is a non-invasive, painless, fast, and low-cost exam that provides neurophysiological data for diagnosis of NMOSD.